2013
DOI: 10.1016/j.jelechem.2012.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Combined studies of DFT atomistic modelling and in situ FTIR spectroscopy on surface oxidants and CO oxidation at Ru electrodes

Abstract: Combined studies of DFT atomistic modelling and in-situ FTIR spectroscopy on surface oxidants and CO oxidation at Ru electrodes, Journal of Electroanalytical Chemistry (2012), doi: http://dx.doi.org/10. 1016/j.jelechem.2012.10.027 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…However, at higher potentials, significant oxidation of methanol to CO 2 in acid solution and to bicarbonate and formate in alkaline solution, was observed, which was attributed to the formation of an active RuO 2 (100) phase on Ru(0001). [11][12][13][14][15] Wang et al also found that RuO 2 (100) was more active than Ru(0001) in CO oxidation. 16 In comparison with the most stable RuO 2 (110) surface, [17][18][19] the RuO 2 (100) with the higher surface energy was less investigated in the literature.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…However, at higher potentials, significant oxidation of methanol to CO 2 in acid solution and to bicarbonate and formate in alkaline solution, was observed, which was attributed to the formation of an active RuO 2 (100) phase on Ru(0001). [11][12][13][14][15] Wang et al also found that RuO 2 (100) was more active than Ru(0001) in CO oxidation. 16 In comparison with the most stable RuO 2 (110) surface, [17][18][19] the RuO 2 (100) with the higher surface energy was less investigated in the literature.…”
mentioning
confidence: 97%
“…9,10 The electrochemical behavior of the Ru singlecrystal plane, and the chemistry of small organic molecules has been investigated. [11][12][13][14][15] The surface oxidation states, i.e., (2 Â 2)-O and (1 Â 1)-O were identified over a potential range on Ru(0001). [11][12][13][14][15] No oxidation of methanol is observed at potentials below 0.8 V, suggesting that the surface oxides block the Ru(0001) physically for methanol adsorption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption energy of CO was found to be around 0.6 eV larger in the honeycomb structure. However, note that in both considered structures the O:CO ratio was 2:1, i.e., none of them corresponded to the low temperature CO saturation coverage (the one with crowded CO molecules in the empty space of the (2×1)-O layer) found experimentally by Kostov et al 17 Also the energetics and minimum energy path for CO oxidation have been studied for different adsorbate structures and coverages, including the p(2×2)-O+CO structure, [21][22][23] the p(2×1)-O with CO in hcp sites in a O:CO ratio of 2:1, 23,24 the 0.5 ML O honeycomb structure, 24,25 and two very low coverage phases consisting in one O and one CO in a 5×5 cell and three O and one CO in the same cell. 26 A general result of these studies was that the main responsible of the activation barrier that hinders CO oxidation at Ru(0001) in UHV conditions is the energy required to destabilize and move the atomic oxygen from its adsorption site.…”
Section: Introductionmentioning
confidence: 92%
“…Several explanations have been offered for the role of M 2nd in improving the catalytic performance: (1) it may change the morphology of Pt clusters and help anchor Pt and maintain it in a state of high dispersion [14,[20][21][22][23][24][25][26]; (2) it may convert the poisonous species into harmless compound in the reaction [2,27]; (3) in bonding with Pt, it may change the electronic properties and geometric features of Pt thereby decreasing the adsorption of poisonous species on Pt [18,24,[28][29][30][31][32][33]; and (4) in association with Pt, it may modify the catalytic properties of Pt [34][35][36][37][38]. To discriminate the role of M 2nd in improving the catalytic performances, it is crucial to determine the structure of the catalysts, specifically, the extent of bimetallic interaction.…”
Section: Introductionmentioning
confidence: 99%